2014
DOI: 10.5430/jnep.v4n12p42
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel perspectives in clinical learning environments' assessment: An insight on levels involved in planning nursing education

Abstract: Background: Clinical learning in nursing education is workplace-based and it involves both learning and organizational factors. Students could experience these factors both at individual and at group level. This study aimed to assess clinical learning environment as a multilevel phenomenon, by grouping students' perceptions at different organizational levels. Method:A cross-sectional multilevel design has been conducted. 3 Italian Universities, 6 Hospitals and 73 wards have been involved in the study during 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…In fact, work engagement and the clinical learning environment are usually approached in research at the individual level (Simpson , Tomietto et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In fact, work engagement and the clinical learning environment are usually approached in research at the individual level (Simpson , Tomietto et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…, Tomietto et al . ). Specifically, this study demonstrated that work engagement, in nursing work‐teams, is effective in improving students’ clinical learning.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the Lithuanian Bachelors of nursing degree, students are required to perform clinical placements of no less than 50 % of their total education time, in line with the European Council recommendation that the clinical component should comprise 50 % of the nursing education programme and take place in healthcare settings (Directive 2013/55/EU). The clinical learning environment (CLE) is a multilevel phenomenon which consist of a pedagogical atmosphere, the leadership style of the ward manager, the premises of nursing, and supervisory relationships (Tomietto et al, 2014). Nursing programmes and healthcare facility leaders must evaluate the CLE, ensuring learning objectives are met, to better prepare students for practice (Flott & Linden, 2016).…”
Section: Introductionmentioning
confidence: 99%